ATC enhancement with SSSC-knowledge inference based intelligent controller tuning - Pandey R.K.; Gupta D.K. (My University, 2025)
The paper presents an analysis of an intelligent controller tuning for transmission line available transfer capability (ATC) enhancement employing coordinated control strategy of power system stabilizers (PSS) and Static synchronous series compensator (SSSC). A concept of Dynamic knowledge inference (DKI) mechanism has been proposed for tuning of PSS and SSSC to damp the inter-area oscillations. The optimal parameters of controllers have been derived from Knowledge domain developed using Gravitational Search Algorithm (GSA) and Firefly Algorithm (FA). In the present paper, SSSC has been used as a supplementary controller to assist PSS functionality when it fails to stabilize at certain operating conditions. A Sample six area system has been considered to demonstrate the effectiveness of the method proposed. The study demonstrates the controlled states response even with the operational shift. © 2016 IEEE.